2022
DOI: 10.1101/2022.12.03.518999
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Astrocyte transcriptomic changes along the spatiotemporal progression of Alzheimer’s disease

Abstract: Astrocytes play a critical role in brain homeostasis and normal functions but their changes along the spatiotemporal progression of Alzheimer's disease (AD) neuropathology remain largely unknown. Here we performed single-nucleus RNA-sequencing on brain regions along the stereotypical progression of AD pathology from donors ranging the entire normal aging-AD continuum comprising 628,943 astrocyte nuclei from 32 donors across 5 brain regions. We discovered temporal gene-expression-trajectories with gene sets dif… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1
1

Relationship

3
3

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 49 publications
(69 reference statements)
1
5
0
Order By: Relevance
“…A similar conclusion was reached in a comprehensive study by Serrano-Pozo et al ( 2022 ), who analyzed five brain regions consecutively affected during AD progression. The authors identified two reactive astrocyte clusters characterized by a reactive signature.…”
Section: Alzheimer's Diseasesupporting
confidence: 81%
“…A similar conclusion was reached in a comprehensive study by Serrano-Pozo et al ( 2022 ), who analyzed five brain regions consecutively affected during AD progression. The authors identified two reactive astrocyte clusters characterized by a reactive signature.…”
Section: Alzheimer's Diseasesupporting
confidence: 81%
“…3 D ). Of note, nonendothelial cell types collected are concurrently being analyzed in separate studies ( Serrano-Pozo et al, 2022 ; Alzheimer DataLENS, 2023 ).…”
Section: Resultsmentioning
confidence: 99%
“…While here, we focused on brain myeloid cells, our parent study included snRNA-seq of all brain cell types. We found that microglia are relatively uniform across the neocortex, whereas astrocytes and endothelial cells have brain region-specific signatures [ 6 , 46 ]. Astrocytes develop an apparent decreased activation (“burnt out”) phenotype in end-stage disease [ 46 ], whereas we see no evidence of an analogous state for microglia.…”
Section: Discussionmentioning
confidence: 99%